Pitch-based carbon fiber, method for producing the same, and fiber-reinforced plastic
Patent Information
- Application Number
- CN202280039091.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-02
- Filing Date
- 2022-06-02
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-06-02
AI Technical Summary
[0030]根据本公开的一个实施方式,提供可得到抗拉强度优异的沥青系碳纤维的沥青系碳纤维的制造方法。
Smart Images

Figure CN117441042B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to pitch-based carbon fibers, methods for manufacturing the same, and fiber-reinforced plastics. Background Technology
[0002] Pitch-based carbon fibers are widely used in various applications, including fiber-reinforced plastics. Such pitch-based carbon fibers are disclosed, for example, in Patent Document 1, Patent Document 2, and Patent Document 3.
[0003] Patent Document 1: Japanese Patent Application Publication No. 60-155714
[0004] Patent Document 2: Japanese Patent Application Publication No. 61-006316
[0005] Patent Document 3: Japanese Patent Publication No. 5-29689 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] Techniques related to pitch-based carbon fibers have been studied extensively, exemplified by Patent Document 1. However, current techniques for improving the tensile strength of pitch-based carbon fibers are insufficient. Patent Documents 2 and 3 suggest room for improvement in enhancing tensile strength while maintaining a high tensile modulus. Generally, a higher graphitization temperature (graphitization temperature) leads to a higher tensile modulus, but a manufacturing method is needed to produce a higher tensile modulus at the same graphitization temperature.
[0008] This disclosure is made in view of the following situation, and one embodiment of this disclosure aims to solve the problem of providing a method for manufacturing pitch-based carbon fibers that can produce pitch-based carbon fibers with excellent tensile strength.
[0009] The problem to be solved by other embodiments of this disclosure is to provide pitch-based carbon fibers with excellent tensile strength.
[0010] Other embodiments of this disclosure aim to solve the problem of providing fiber-reinforced plastics using the aforementioned pitch-based carbon fibers.
[0011] Methods for solving problems
[0012] This disclosure includes the following solutions.
[0013] <1> A pitch-based carbon fiber has a defect number density of less than 40 defects / m, and the shape of the cross section perpendicular to the length direction is circular or elliptical with an flatness ratio of less than 0.25, and has a boundary surface in the diameter direction of the circular cross section or the major axis direction of the elliptical cross section.
[0014] <2> according to <1> The pitch-based carbon fiber, wherein the area occupied by the graphene sheet oriented at an orientation angle of 60° to 120° relative to the boundary surface accounts for more than 60% of the area of the aforementioned cross section.
[0015] <3> according to <2> The pitch-based carbon fiber, wherein the cross-sectional shape is circular or elliptical with a flatness ratio of less than 0.2.
[0016] <4> according to <1> ~ <3> The pitch-based carbon fiber according to any one of the above-mentioned methods, wherein the defect number density is less than 30 defects / m.
[0017] <5> according to <1> ~ <4> The pitch-based carbon fiber according to any one of the following methods has a tensile modulus of elasticity of 400 GPa or higher.
[0018] <6> according to <5> The pitch-based carbon fiber has a tensile modulus of 440 GPa or higher.
[0019] <7> A method for manufacturing pitch-based carbon fibers includes a melt spinning process in which molten anisotropic pitch is ejected from a spinning nozzle and spun into fibers.
[0020] The ratio of the length of the longer side of the circumscribed rectangle to the length of the shorter side of the circumscribed rectangle exceeds 1.
[0021] The viscosity of molten anisotropic bitumen is 20 Pa·s to 80 Pa·s.
[0022] <8> according to <7> The method for manufacturing pitch-based carbon fiber, wherein the ratio is 1.5 to 10.0.
[0023] <9> according to <7> or <8> In the method for manufacturing pitch-based carbon fiber, the shape of the ejection orifice is rectangular or elliptical.
[0024] <10> according to <7> ~ <9> The method for manufacturing pitch-based carbon fiber according to any one of the above-mentioned methods, wherein the viscosity of the anisotropic pitch is 30 Pa·s to 60 Pa·s.
[0025] <11> according to <7> ~ <10> In any one of the methods for manufacturing pitch-based carbon fibers, the spinning speed in the melt spinning process is 200 m / min to 500 m / min.
[0026] <12> according to <7> ~ <11> The method for manufacturing pitch-based carbon fiber according to any one of the above-mentioned melt spinning process includes a graphitization process that involves heat-treating the carbonized pitch-based carbon fiber precursor to graphitize it after the melt spinning process.
[0027] The temperature of the heat treatment in the graphitization process is 2000℃~2900℃.
[0028] <13> A fiber-reinforced plastic comprising <1> ~ <6> The pitch-based carbon fiber as described in any one of the above.
[0029] Invention Effects
[0030] According to one embodiment of the present disclosure, a method for manufacturing pitch-based carbon fibers that can produce pitch-based carbon fibers with excellent tensile strength is provided.
[0031] According to other embodiments of this disclosure, pitch-based carbon fibers with excellent tensile strength are provided.
[0032] According to other embodiments of this disclosure, fiber-reinforced plastics using the above-described pitch-based carbon fibers are provided. Attached Figure Description
[0033] Figure 1 This is an example of a Weibull distribution plot (also known as a Weibull plot).
[0034] Figure 2 This is a schematic diagram showing an example of a cross-section of pitch-based carbon fiber.
[0035] Figure 3 This is a schematic diagram showing an example of a cross-section of pitch-based carbon fiber.
[0036] Figure 4 This is a schematic diagram showing an example of a cross-section of pitch-based carbon fiber.
[0037] Figure 5 This is an SEM image representing an example of a cross-section of pitch-based carbon fiber.
[0038] Figure 6 yes Figure 5 An example of a binarized SEM image.
[0039] Figure 7 yes Figure 6 An example of editing a binarized image.
[0040] Figure 8 This is a diagram showing an example of the orientation angle of a graphene sheet.
[0041] Figure 9 This is a schematic diagram showing an example of the cross-section of a spinning nozzle.
[0042] Figure 10 This is a schematic diagram showing an example of the ejection orifice of a spinning nozzle. Detailed Implementation
[0043] The following provides a detailed description of the pitch-based carbon fiber and its manufacturing method disclosed herein.
[0044] In this disclosure, the numerical range represented by “~” refers to the range in which the values recorded before and after “~” are respectively the minimum and maximum values.
[0045] Within the numerical range described in stages in this disclosure, the upper or lower limit value described in a certain numerical range can also be replaced by the upper or lower limit value of other numerical ranges described in stages. Furthermore, within the numerical range described in this disclosure, the upper or lower limit value described in a certain numerical range can also be replaced by the values shown in the embodiments.
[0046] In this disclosure, a combination of two or more preferred solutions is a more preferred solution.
[0047] In this disclosure, the amount of each component refers to the total amount of the multiple substances unless otherwise specified, in the case where there are multiple substances that conform to each component.
[0048] In this disclosure, the term "process" not only includes independent processes, but also includes any process that can achieve the desired purpose of the process, even if it cannot be clearly distinguished from other processes.
[0049] The accompanying drawings referenced in the following description are illustrative and schematic, and this disclosure is not limited to these drawings. The same symbols denote the same constituent elements. Furthermore, the symbols in the drawings are sometimes omitted.
[0050] <Pitch-based carbon fiber>
[0051] For the pitch-based carbon fiber of this disclosure, the defect number density is less than 40 defects / m, the shape of the cross section perpendicular to the length direction is circular or elliptical with an flatness ratio of less than 0.25, and it has a boundary surface in the diameter direction of the circular cross section or the major axis direction of the elliptical cross section.
[0052] Defect number density is the number of defects contained in a unit length of pitch-based carbon fiber. In this disclosure, it refers to a value obtained based on the Weibull distribution diagram. By reducing the defect number density, the tensile strength of pitch-based carbon fibers can be improved.
[0053] The defect number density is related to factors that affect tensile strength, such as the number and size of voids and cracks (hereinafter sometimes referred to as "voids, etc."). Therefore, by reducing the number of voids, etc., and decreasing the size of voids, etc., the defect number density can be reduced and tensile strength increased.
[0054] The following section provides a detailed explanation of the method for obtaining the defect number density based on the Weibull distribution map.
[0055] For pitch-based carbon fibers of length L [m], the defect number density λ [number / m] is expressed by the following equation (1).
[0056]
[0057] In equation (1), σ, β, γ and L0 are as follows.
[0058] σ: Tensile strength [GPa] of each single fiber in pitch-based carbon fiber (N single fibers)
[0059] β: The width of the probability distribution of the tensile strength of each single fiber in pitch-based carbon fiber (N single fibers).
[0060] (Shape parameter (Weibull modulus))
[0061] γ: Tensile strength per unit length of pitch-based carbon fiber, calculated from the probability distribution of the tensile strength of each individual fiber.
[0062] (Scale parameter)
[0063] L0: The reference length (1m) of pitch-based carbon fiber.
[0064] The fracture probability F(L) of pitch-based carbon fiber at tensile strength σ (hereinafter, sometimes referred to as "fracture probability F") is expressed by the following equation (2).
[0065] F(L)=1-exp(-λL)...(2)
[0066] Equation (2) is based on a model in which the entire chain is destroyed when the weakest link is broken when the chain is stretched (the weakest chain model).
[0067] If we substitute equation (1) into equation (2), we can obtain the following equation (3).
[0068]
[0069] If we expand equation (3), we can obtain the following equation (4).
[0070]
[0071] Equation (4) is a linear function of ln[-ln(1-F)] and lnσ, and a Weibull distribution diagram is given.
[0072] The following describes the method for determining the fracture probability F and the tensile strength σ of each single fiber through experiments.
[0073] According to JIS R 7606:2000, N tensile strengths are obtained by conducting tensile tests on N pitch-based carbon fibers. For a certain tensile strength σ among the N tensile strengths, when the number of pitch-based carbon fibers that break below tensile strength σ is n, the breakage probability F at tensile strength σ (i.e., the proportion of pitch-based carbon fibers with tensile strength below σ) is expressed by the following equation (5).
[0074] F = n / N…(5)
[0075] Substituting the tensile strength σ and the fracture probability F at tensile strength σ into equation (4), we plot ln[-ln(1-F)] and lnσ. Furthermore, we calculate the fracture probability for other tensile strengths in the same way and plot them accordingly. Thus, we can obtain N plots. N is set to 30 or more. For example, we obtain... Figure 1 The Weibull distribution map shown is shown below.
[0076] By fitting equation (4) to the Weibull distribution using the least squares method, a fitted straight line is obtained. For example, we get... Figure 1 The fitted straight line is as shown in the figure.
[0077] β and γ are obtained from the slope of the fitted straight line and the values of the slice. Furthermore, the average tensile strength (σ) is calculated from the results of tensile tests. av Substituting σ into equation (1) av As σ, and further substituting β and γ, we obtain the defect number density λ. The defect number density λ obtained in this way is the average defect number density λ. av , which is the defect number density of the pitch-based carbon fiber shown in this application.
[0078] By operating as described above, the defect number density of pitch-based carbon fibers can be obtained based on the Weibull distribution map.
[0079] The number of pitch-based carbon fibers N used in the tensile test is preferably 30 or more. There is no particular upper limit to the number of fibers N, but for example, 50 fibers is preferable.
[0080] The length of the pitch-based carbon fiber used in the tensile test was set to 25 mm.
[0081] Since pitch-based carbon fibers tend to have higher tensile strength when the defect number density is lower, a lower defect number density is preferred. For example, a defect number density of 30 defects / m or less is preferred, more preferably 25 defects / m or less, and even more preferably 10 defects / m or less. The lower limit of the defect number density is not particularly limited, but is typically around 1 defect / m.
[0082] The cross-section (hereinafter sometimes simply referred to as the "section") of pitch-based carbon fibers perpendicular to their length direction is circular or elliptical with an aspect ratio of 0.25 or less. This makes it easier to reduce the defect number density. Here, "perpendicular" means 90° ± 15°.
[0083] The flatness ratio is a value obtained by subtracting from 1 the ratio of the length of the shorter side of the circumscribed rectangle to the length of the longer side of the circumscribed rectangle. The circumscribed rectangle is the rectangle that is circumscribed in the ellipse and has the smallest area.
[0084] There is no particular limitation on the diameter of pitch-based carbon fibers, but for example, 5μm to 20μm is preferred.
[0085] The shape, flatness, and diameter of the cross-section of pitch-based carbon fiber are obtained by the following method: according to JIS R 7606:2000, a laser shape measuring device is used, with the measuring range set to 0° to 180°, and the cross-section of the pitch-based carbon fiber is rotated every 10° to measure the shape of the outer perimeter of the cross-section. A commercially available laser shape measuring device is preferred; for example, the "Laser Scanning Micrometer LSM-500S" manufactured by Mitutoyo can be cited.
[0086] When the cross-section is elliptical, the major and minor axes are determined from the shape of the outer perimeter of the cross-section. The equivalent circle diameter (the square root of the product of the major and minor axes) calculated from the area of the ellipse is set as the diameter of the pitch-based carbon fiber.
[0087] From the viewpoint of more easily reducing defect number density, the shape of the cross-section perpendicular to the length direction is preferably circular or elliptical with a flatness ratio of 0.2 or less, more preferably circular or elliptical with a flatness ratio of 0.18 or less, and even more preferably circular or elliptical with a flatness ratio of 0.15 or less. The lower limit of the flatness ratio is not particularly limited in the case of an elliptical shape, but from the viewpoint of more easily reducing defect number density, it is preferably 0.01 or more.
[0088] Pitch-based carbon fibers include graphene sheets. Graphene sheets are sheet-like materials with a lattice structure in which carbon atoms are bonded in a hexagonal shape on a plane.
[0089] The structure of pitch-based carbon fibers varies depending on the state (e.g., orientation) of the graphene sheet, and can be categorized into radial structure, onion structure, random structure, etc., but the radial structure is preferred.
[0090] In the radial structure, multiple graphene sheets extend along the length of the pitch-based carbon fiber. In addition, in the cross-section, multiple graphene sheets extend from a specified position toward the outer periphery of the cross-section.
[0091] The graphene sheet can be in contact with or separated from the positions specified above. Furthermore, the graphene sheet can be in contact with or separated from the outer periphery of the cross-section.
[0092] The graphene sheets should ideally be in contact with each other at the positions specified above, but they may not be in contact.
[0093] For example, Figure 2 As shown, the cross-section of the pitch-based carbon fiber 100 is elliptical, and multiple graphene sheets 10 extend from the boundary surface 30 (at the position specified above) along the major axis of the ellipse toward the outer periphery of the cross-section. In this way, the graphene sheets 10 are oriented relative to the boundary surface 30 along the major axis of the cross-section. Such a pitch-based carbon fiber structure is sometimes referred to as a "flat radial structure".
[0094] In other implementations, such as Figure 3 As shown, the cross-section of the pitch-based carbon fiber 102 is circular, and multiple graphene sheets 10 extend from the boundary surface 32 (the position specified above) in the diametrical direction of the circle toward the outer periphery of the cross-section. In this way, the graphene sheets 10 are oriented relative to the boundary surface 32 in the diametrical direction of the cross-section.
[0095] In other implementations, such as Figure 4 As shown, the cross-section of the pitch-based carbon fiber 104 is circular, and multiple graphene sheets 10 extend radially from the center 34 (the position specified above) of the circle toward the outer periphery of the cross-section. Such a pitch-based carbon fiber structure is sometimes referred to as a "simple radial structure".
[0096] Like this, Figure 3 The pitch-based carbon fiber shown Figure 4 For the pitch-based carbon fibers shown, although the cross-sectional shape is the same (circular), the extension shape of the graphene sheets in the cross-section is different.
[0097] From the perspective of making it easier to reduce the defect number density, it is preferable to orient the graphene sheet relative to the boundary surface of the cross section in the diameter or long axis direction of the pitch-based carbon fiber.
[0098] The area occupied by the graphene sheet (hereinafter sometimes referred to as the "specific area") of the pitch-based carbon fiber at an orientation angle of 60° to 120° relative to the boundary surface of the cross section with respect to the diameter or long axis direction is preferably 60% or more relative to the area of the cross section. This makes it easier to reduce the defect number density.
[0099] The area ratio of a specific region is obtained as follows.
[0100] Using a scanning electron microscope (SEM), randomly selected sections of pitch-based carbon fibers were observed along a direction perpendicular to the section to obtain SEM images. Thus, for example, we obtained... Figure 5 The image shows a SEM image of the cross-section of pitch-based carbon fiber as shown. For example, a JSM-6500F SEM manufactured by Nippon E. Co., Ltd. can be used. Regarding the acquisition conditions for the SEM image, the magnification only needs to be sufficient to obtain the cross-section of a single fiber (e.g., 7000x to 10000x, or 10000x for pitch-based carbon fiber with a diameter of approximately 7μm). The accelerating voltage is not specifically specified, but is preferably, for example, 5kV to 15kV.
[0101] The SEM image was analyzed using the image processing software "ImageJ (vl.52)". Specifically, the SEM image was binarized to obtain a binarized image of the cross-section. Thus, for example, the following was obtained: Figure 6 A binarized image as shown in the image.
[0102] Using ImageJ (vl.52), an edit is performed on a binarized image, depicting the black portions of the image as line segments, to obtain an edited image of the cross-section. Thus, for example, we obtain... Figure 7 An edited image as shown.
[0103] For image editing, the straightness of line segments in the cross-section is evaluated using fractal dimension analysis to determine line segments with a value of D = 1.2 or less. Line segments with a value of D = 1.2 or less are defined as "graphene sheets". ImageJ (vl.52) is an open-source, public-domain image processing software.
[0104] The line segment with the maximum length of the given cross-section contour in the edited image (i.e., the maximum length of the straight line connecting any two points of the contour, which is the diameter in the case of a circular cross-section and the major axis in the case of an elliptical cross-section) is defined as the "boundary surface".
[0105] The image is parsed using the program described in "Python (v3)" (open source), covering the entire cross-section, to determine the orientation angle of each graphene sheet (line segments with D = 1.2 or less) relative to the boundary surface. The angle at the intersection of the line containing the boundary surface and the line containing the graphene sheet is then set as the orientation angle. For example, as... Figure 8 As shown, the orientation angle α is obtained from the angle at the intersection of the straight line 36 containing the boundary surface and the straight line 12 containing the graphene sheet. For example, in Figure 8 The cross-section shown contains a large area of short graphene sheets. Figure 8The orientation angle is evaluated across the entire cross-section, regardless of the length of the graphene sheet (the area in the middle, upper left and lower right).
[0106] Using ImageJ (vl.52), the area (specific region) occupied by graphene sheets oriented at an angle of 60° to 120° (line segments with D = 1.2 or less and an orientation angle of 0° to 120°) is set to black for display, and the specific region in the cross-section is identified. Using ImageJ (vl.52), the area of the specific region and the area of the cross-section are calculated. The area of the specific region is divided by the area of the cross-section to obtain the ratio of the area of the specific region.
[0107] For the same cross section as the pitch-based carbon fiber, five identical measurements were performed, and the average of the area ratios of the specific regions obtained from the five measurements was set as the area ratio of the specific regions of the pitch-based carbon fiber.
[0108] From the viewpoint that it is easier to reduce the defect number density, for graphene sheets oriented at an orientation angle of 60° to 120°, the average value of the orientation angle is more preferably 70° to 110°.
[0109] From the viewpoint of more easily reducing defect number density, the ratio of the area of a specific region is more preferably 70% or more. There is no particular upper limit to the ratio of the area of a specific region, but from the viewpoint of more easily reducing defect number density, it is preferably 95% or less.
[0110] The higher the tensile strength of the pitch-based carbon fiber, the better. For example, it is preferred to have a tensile strength of 3600 MPa or more, more preferably 3800 MPa or more, and even more preferably 4000 MPa or more.
[0111] The tensile strength of pitch-based carbon fibers was determined according to JIS R 7606:2000. The average value of N tensile strengths obtained from the above tensile tests for the Weibull distribution was set as the tensile strength of the pitch-based carbon fibers.
[0112] From the perspective of further improving mechanical properties, the higher the tensile modulus of pitch-based carbon fibers, the better, for example, preferably 400 GPa or more, more preferably 440 GPa or more, and even more preferably 460 GPa or more.
[0113] The tensile modulus of elasticity of pitch-based carbon fibers was determined according to JIS R 7606:2000. The tensile modulus of elasticity was also determined in the tensile test described above for the Weibull distribution diagram. The average of the N tensile moduli of elasticity obtained from N pitch-based carbon fibers was set as the tensile modulus of elasticity of the pitch-based carbon fiber.
[0114] <Manufacturing Methods of Pitch-Based Carbon Fibers>
[0115] The method for manufacturing pitch-based carbon fibers disclosed herein is not particularly limited, but the method for manufacturing pitch-based carbon fibers described below may be suitable.
[0116] The method for manufacturing pitch-based carbon fibers disclosed herein includes:
[0117] The molten anisotropic pitch is ejected from the spinning nozzle and then spun into a melt spinning process.
[0118] The ratio of the length of the longer side of the circumscribed rectangle to the length of the shorter side of the circumscribed rectangle exceeds 1.
[0119] The viscosity of molten anisotropic bitumen is 20 Pa·s to 80 Pa·s.
[0120] In addition to the melt spinning process, the manufacturing method of pitch-based carbon fiber also includes the following non-melting process, carbonization process, and graphitization process. Each process is described in detail below.
[0121] [Melt spinning process]
[0122] In the melt spinning process, molten anisotropic pitch is ejected from the spinning nozzle and spun into fibers.
[0123] (Anisotropic bitumen)
[0124] Anisotropic bitumen contains an intermediate phase in which bitumen molecules are arranged in a planar manner. The intermediate phase becomes graphene sheets through a graphitization process, and is a precursor to graphene sheets.
[0125] Examples of raw materials for anisotropic pitch include coal tar, coal tar pitch, and coal liquefaction, as well as heavy coal oils such as atmospheric distillation, vacuum distillation residues of petroleum, and petroleum-based heavy oils such as tar and pitch produced as byproducts of these heat treatments. Anisotropic pitch can be obtained by appropriately combining heat treatment, solvent extraction, and hydrogenation treatment on such raw materials.
[0126] The proportion of the mesophase in the anisotropic pitch is preferably 60% or more, more preferably 70% or more. This makes it easier to express the physical properties of pitch-based carbon fibers, especially the tensile modulus of elasticity.
[0127] The proportion of the intermediate phase is determined as follows.
[0128] Samples were randomly selected from anisotropic asphalt and observed using a polarizing microscope at magnifications ranging from 10 to 100. For randomly selected fields of view, the area of the entire field and the area of the intermediate phase were measured. The ratio of the area of the intermediate phase to the area of the entire field of view was defined as the proportion of the intermediate phase. That is, the proportion of the intermediate phase is the area ratio of the intermediate phase relative to the anisotropic asphalt.
[0129] The melting point of anisotropic bitumen is not particularly limited, but it is preferably 260°C to 320°C, and more preferably 270°C to 310°C.
[0130] From the perspective of reducing foreign matter in anisotropic asphalt and more easily improving tensile strength, the quinoline-insoluble component in anisotropic asphalt is preferably 20% by mass or less. The quinoline-insoluble component can be determined using known methods.
[0131] (Spinning nozzle)
[0132] In a spinning nozzle that sprays anisotropic bitumen, the ratio of the length of the long side of the circumscribed rectangle to the length of the short side of the circumscribed rectangle to the shape of the spray hole (hereinafter sometimes referred to as the "aspect ratio") exceeds 1. The circumscribed rectangle is the rectangle that is circumscribed to the elliptical shape of the spray hole and has the smallest area.
[0133] It should be noted that the shape of the nozzle is not limited to ellipse; it can also be rectangular. When the nozzle is rectangular, the ratio of the length of the longer side to the length of the shorter side (hereinafter sometimes referred to as the "aspect ratio") exceeds 1.
[0134] Because the aspect ratio of the ejector hole exceeds 1, the anisotropy of the ejector hole shape is greater compared to the case where the aspect ratio is 1.
[0135] When molten anisotropic bitumen passes through the nozzle of a spinning nozzle, the intermediate phase in the anisotropic bitumen is oriented, but the orientation morphology varies depending on the shape of the nozzle.
[0136] When the nozzle shape is circular (length-to-width ratio is 1), the intermediate phase of the resulting linear body (hereinafter sometimes referred to as "pitch-based carbon fiber precursor") is, for example, similar to... Figure 4 The graphene sheet shown has the same morphology, oriented radially from the center of the cross-section towards the outer periphery. Due to the low anisotropy of the nozzle shape, the mesophase is easily oriented uniformly from the center of the cross-section.
[0137] By performing infusible melting, carbonization, and graphitization processes on a pitch-based carbon fiber precursor with a mesophase oriented radially from the center of the cross-section towards the periphery (hereinafter sometimes referred to as "morphology 1"), it is possible to obtain, for example, a carbon fiber precursor with... Figure 4 The graphene sheet shown is an oriented pitch-based carbon fiber.
[0138] In contrast, when the aspect ratio of the ejection orifice exceeds 1, the intermediate phase in the resulting pitch-based carbon fiber precursor is, for example, similar to... Figure 2 or Figure 3 The graphene sheet shown is oriented in the same manner from the boundary of the cross-section toward the outer periphery. This is because the shape of the ejector hole is highly anisotropic, and its orientation varies depending on the portion through which the intermediate phase passes.
[0139] By performing infusible melting, carbonization, and graphitization processes on pitch-based carbon fiber precursors with an orientation of the mesophase from the boundary surface of the cross-section towards the outer periphery (hereinafter sometimes referred to as "morphology 2"), it is possible to obtain, for example, a carbon fiber precursor with... Figure 2 or Figure 4 The graphene sheet shown is an oriented pitch-based carbon fiber.
[0140] In addition to setting the aspect ratio of the spinning nozzle orifice to be greater than 1, the viscosity of the molten anisotropic bitumen is also set to 20 Pa·s to 80 Pa·s. This makes it easier for the mesophase in the anisotropic bitumen to orient from the boundary surface of the cross-section towards the outer periphery as the molten anisotropic bitumen passes through the spinning nozzle orifice. It should be noted that the viscosity referred to here is the melting temperature in the storage region before exiting the spinning nozzle (i.e.,...). Figure 9 The viscosity of anisotropic asphalt at a temperature of 70°C at the inlet section.
[0141] Furthermore, by satisfying the above aspect ratio and viscosity, it becomes easy to set the defect number density to 40 or less per m.
[0142] Furthermore, by satisfying the above aspect ratio and viscosity, it becomes easy to set the orientation angle of the graphene sheet relative to the above boundary surface to a range of 60° to 120°. In addition, it becomes easy to set the area ratio of a specific region to 60%.
[0143] The viscosity of the molten anisotropic bitumen is set to 20 Pa·s to 80 Pa·s, preferably 25 Pa·s to 70 Pa·s, and more preferably 30 Pa·s to 60 Pa·s.
[0144] The viscosity of anisotropic asphalt was determined using the following method. It should be noted that the viscosity (at 320°C) determination method is described below using anisotropic asphalt with a melting temperature of 320°C as an example. Viscosity was measured using a concentric double tube and a high-temperature cell, employing a Rheomat-30 (manufactured by Contraves), with a shear rate of 4–60 s⁻¹. -1The measurement was performed at a temperature of 320℃.
[0145] The melting temperature of anisotropic bitumen is preferably 320°C to 340°C, and more preferably 323°C to 335°C. It should be noted that the melting temperature here refers to the melting temperature of the anisotropic bitumen in the storage area before it is ejected from the spinning nozzle (i.e., Figure 9 (Temperature at 70°C in the inlet section).
[0146] Compared with the pitch-based carbon fiber precursor of morphology 1, the pitch-based carbon fiber precursor of morphology 2 is less susceptible to thermal shrinkage during the graphitization process.
[0147] Specifically, in morphology 1, the intermediate phase undergoes thermal contraction along the circumferential direction of the cross-section, i.e., the angle between the intermediate phases decreases, thus the outer periphery of the cross-section tends to experience greater thermal contraction. In contrast, in morphology 2, the intermediate phase undergoes thermal contraction in a manner that the distance between the surfaces of the intermediate phases decreases, thus the overall thermal contraction tends to be uniform.
[0148] Based on the above, the pitch-based carbon fiber precursor of morphology 2, compared to the pitch-based carbon fiber precursor of morphology 1, can reduce the impact of thermal shrinkage, and therefore can more easily reduce the defect number density. Therefore, pitch-based carbon fibers obtained from the pitch-based carbon fiber precursor of morphology 2 (e.g., Figure 2 and Figure 3 The pitch-based carbon fiber shown) and the pitch-based carbon fiber obtained from the pitch-based carbon fiber precursor of morphology 1 (e.g. Figure 4 Compared to the pitch-based carbon fiber shown, it is easier to improve tensile strength.
[0149] The aspect ratio of the ejection orifice is not particularly limited as long as it exceeds 1, but is preferably 1.5 to 10.0. By setting the aspect ratio to 1.5 or higher, it becomes easier to obtain the pitch-based carbon fiber precursor of Form 2. Furthermore, by setting the aspect ratio to 10.0 or lower, it becomes easier to form the pitch-based carbon fiber precursor.
[0150] The aspect ratio is more preferably 2.0 to 7.5, and even more preferably 2.5 to 5.0. Furthermore, from the viewpoint of further reducing the defect density and further improving tensile strength, the aspect ratio is even more preferably 3.0 to 5.0.
[0151] The shape of the nozzle is not particularly limited, but it is preferably rectangular or elliptical. This changes the flowability of the anisotropic pitch, making it easier to obtain the pitch-based carbon fiber precursor of Form 2.
[0152] When the nozzle is rectangular, the circumscribed rectangle that is external to the shape of the nozzle should be consistent with the shape of the nozzle. In addition, when the nozzle is rectangular, it is preferable that the corners of the rectangle have curvature.
[0153] Furthermore, when the nozzle is elliptical, the short side of the circumscribed rectangle that is circumscribed to the shape of the nozzle coincides with the minor axis of the ellipse, and the long side of the circumscribed rectangle coincides with the major axis of the ellipse.
[0154] There are no particular limitations on the composition of the spinning nozzle other than those mentioned above. Specific examples are listed below for further explanation.
[0155] Figure 9 The spinning nozzle 200 shown has an ejection orifice 50 and an inlet portion for introducing molten anisotropic bitumen. The shape of the ejection orifice 50 is as follows: Figure 10 The rectangle shown is a rectangle with a short side a and a long side b (length-to-width ratio: b / a).
[0156] Regarding the inlet section 70, the shape of the cross section (hereinafter sometimes referred to as the "cross section of the inlet section") perpendicular to the length direction of the spinning nozzle 200 is not particularly limited, but it is preferable to be circular, elliptical, quadrilateral (square, rectangle, etc.).
[0157] The cross-sectional area of the inlet portion is preferably 10 to 2000 times larger than the area of the nozzle 50. By setting the cross-sectional area of the inlet portion to be 10 times or more larger than the area of the nozzle 50, the pressure during spinning will not become excessively high, thus suppressing the micro-dispersion of anisotropic pitch and making it easier to obtain a high elastic modulus. Furthermore, by setting the cross-sectional area of the inlet portion to be 2000 times or less larger than the area of the nozzle 50, it becomes easier to improve spinnability.
[0158] The area of the inlet section relative to the area of the ejection hole 50 is more preferably 30 to 500 times, and even more preferably 40 to 200 times.
[0159] Figure 9 The cone angle θ of the cone portion 90 shown affects the flowability of the anisotropic pitch within the spinning nozzle, and thus also affects the microstructure formation. Although it varies depending on the cross-sectional area of the inlet portion, the cone angle θ is preferably 60° to 180°. This makes it easier to obtain the pitch-based carbon fiber precursor of Form 2. Furthermore, from the viewpoint of extrusion performance, it is preferable to set the cone angle θ within the aforementioned range. The cone angle θ is more preferably 90° to 150°.
[0160] Figure 9The land length (also known as the nozzle length) L shown is preferably 0.5 MPa to 5.0 MPa, calculated using the Hagen-Poiseuille formula. Setting the pressure loss to 0.5 MPa or higher makes it easier to improve spinnability. Furthermore, setting the pressure loss to 5.0 MPa or lower suppresses the micro-dispersion of anisotropic pitch, making it easier to obtain a high elastic modulus.
[0161] It is advisable to have a rectifier plate upstream of the spinning nozzle.
[0162] Anisotropic asphalt is melted by heating it to a temperature 10°C to 50°C above its melting point, but preferably below 370°C. This makes it easier to prevent clogging of the nozzles caused by carbonization of the anisotropic asphalt.
[0163] The spinning pressure is preferably between 1.0 MPa and 3.0 MPa. By setting the spinning pressure to 1.0 MPa or higher, it becomes easier to improve spinnability. Furthermore, by setting the spinning pressure to 3.0 MPa or lower, it becomes easier to exhibit the physical properties of pitch-based carbon fibers, especially the tensile modulus of elasticity.
[0164] From the viewpoint of more easily achieving the desired diameter, the spraying rate of anisotropic pitch is preferably 0.03 g / min to 0.01 g / min, and the spinning speed of the pitch-based carbon fiber precursor is preferably 200 m / min to 1000 m / min. Furthermore, from the viewpoint of more easily achieving a ratio of the area occupied by graphene sheets oriented at an orientation angle of 60° to 120° relative to the boundary surface of the pitch-based carbon fiber cross-section to the cross-sectional area of 60° to 500 m / min, the spinning speed is more preferably 200 m / min to 500 m / min.
[0165] [Non-melting process]
[0166] In the non-melting process, the pitch-based carbon fiber precursor obtained in the melt spinning process is heat-treated in the presence of oxygen. This prevents the heat-treated pitch-based carbon fiber precursor from melting in subsequent heat treatments.
[0167] For heat treatment atmospheres, examples include air atmospheres, oxidizing gas atmospheres, and mixed gas atmospheres (such as a mixture of nitrogen, oxygen, and oxidizing gases), and it is appropriate to choose the appropriate one.
[0168] The heat treatment temperature is preferably between 120°C and 320°C. Alternatively, the heat treatment can be carried out while simultaneously raising the temperature within the range of 120°C to 320°C. The preferred heat treatment temperature is between 150°C and 300°C.
[0169] The heat treatment time can be set arbitrarily within the range of 30 minutes to 12 hours, preferably within the range of 1 hour to 3 hours.
[0170] [Carbonization process]
[0171] In the carbonization process, the pitch-based carbon fiber precursor, which has undergone heat treatment in the non-melting process, is carbonized by heat treatment in an inactive atmosphere.
[0172] As inert gases, nitrogen, argon, etc. can be used.
[0173] The heat treatment temperature is preferably between 400°C and 1000°C. Alternatively, the heat treatment can be carried out while simultaneously raising the temperature within the range of 400°C to 1000°C.
[0174] The heat treatment time can be set arbitrarily between 5 minutes and 1 hour.
[0175] [Graphitization process]
[0176] In the graphitization process, the pitch-based carbon fiber precursor, which has been carbonized in the carbonization process, is heat-treated in an inactive atmosphere to achieve graphitization.
[0177] As inert gases, nitrogen, argon, etc. can be used.
[0178] The heat treatment temperature is preferably between 2000°C and 3200°C. Furthermore, the heat treatment time is preferably between 1 minute and 1 hour. However, if the heat treatment temperature in the graphitization process becomes too high, equipment and operating costs increase. Additionally, strict measures and management are required to prevent the intrusion of external air. Therefore, it is preferable to set the temperature to 2900°C or below, more preferably 2800°C or below, even more preferably 2500°C or below, and even more preferably 2400°C or below. In the method for manufacturing pitch-based carbon fibers disclosed herein, compared to the manufacturing methods in prior art such as Patent Documents 2 and 3, if the heat treatment temperature in the graphitization process is the same, pitch-based carbon fibers with a higher tensile modulus can be manufactured. In other words, in the method for manufacturing pitch-based carbon fibers disclosed herein, compared to the manufacturing methods in prior art such as Patent Documents 2 and 3, when manufacturing pitch-based carbon fibers with the same level of tensile modulus, the heat treatment temperature in the graphitization process can be set at a lower setting.
[0179] Through the above processes, pitch-based carbon fibers can be obtained.
[0180] <Fiber-reinforced plastics>
[0181] The fiber-reinforced plastics disclosed herein include the pitch-based carbon fibers of this disclosure.
[0182] There are no particular limitations on the manufacturing method of fiber-reinforced plastics; well-known manufacturing methods are preferred. For example, it is preferable to prepare a prepreg by impregnating pitch-based carbon fibers with resin, and then perform molding processes such as PCM (Pre-preg Compression Molding) to obtain fiber-reinforced plastics. Alternatively, it is preferable to obtain fiber-reinforced plastics by using pitch-based carbon fibers and resin, and performing molding processes such as SMC (Sheet Molding Compound) or RTM (Resin Transfer Molding).
[0183] Examples of resins include thermosetting resins and thermoplastic resins.
[0184] Examples of thermosetting resins include epoxy resins, unsaturated polyester resins, vinyl ester resins, bismaleimide resins, phenolic resins, cyanate ester resins, and polyimides.
[0185] Examples of thermoplastic resins include nylon, polypropylene, polyphenylene sulfide, polyetherimide, polycarbonate, polyethylene terephthalate, and polyetheretherketone.
[0186] The fiber-reinforced plastic disclosed herein has excellent strength due to the inclusion of the pitch-based carbon fiber of this disclosure, making it suitable for a variety of applications.
[0187] Example
[0188] The present disclosure will be further illustrated below with examples. However, the present disclosure is not limited to these examples.
[0189] Manufacturing of Pitch-Based Carbon Fibers
[0190] [Example 1]
[0191] Using anisotropic bitumen (melting point: 302.1℃), through Figure 9 and Figure 10 The spinning nozzle shown (orifice shape: rectangular, aspect ratio: 2.5, cone angle: 120°) is used for melt spinning to obtain pitch-based carbon fiber precursors. The melting temperature of the molten anisotropic pitch (near the orifice) is 330°C, and the viscosity is 40 Pa·s. Furthermore, the pitch flow rate is 0.035 g / min to 0.090 g / min, the spinning pressure is 2 MPa to 3 MPa, and the spinning speed is 350 m / min.
[0192] By subjecting the obtained pitch-based carbon fiber precursor to a non-melting process (under a mixed gas atmosphere of nitrogen, oxygen and oxidizing gases), a carbonization process, and a graphitization process (heat treatment temperature 2000℃), the pitch-based carbon fiber of Example 1 was obtained.
[0193] [Example 2]
[0194] The anisotropic pitch was melted at a melting temperature of 325°C, and the viscosity was set to 75 Pa·s. Otherwise, the same procedure as in Example 1 was followed to obtain the pitch-based carbon fiber of Example 2.
[0195] [Example 3]
[0196] Except for changing the aspect ratio of the spinning nozzle to 5.0, the pitch-based carbon fiber of Example 3 was obtained by operating in the same manner as in Example 1.
[0197] [Comparative Example 1]
[0198] The shape of the nozzle orifice of the spinning nozzle was set to circular (length-to-width ratio: 1.0), and the spraying rate of the anisotropic pitch was set to 0.035 g / min to 0.040 g / min. Otherwise, the pitch-based carbon fiber of Comparative Example 1 was obtained by operating in the same manner as in Example 1.
[0199] [Comparative Example 2]
[0200] The anisotropic pitch was melted at a melting temperature of 320°C, and the viscosity was set to 120 Pa·s. Otherwise, the same procedure as in Example 1 was followed to obtain the pitch-based carbon fiber of Comparative Example 2.
[0201] [Comparative Example 3]
[0202] The anisotropic pitch was melted at a melting temperature of 310°C, and the viscosity was set to 150 Pa·s. Otherwise, the same procedure as in Example 1 was followed to obtain the pitch-based carbon fiber of Comparative Example 3.
[0203] <Evaluation of Pitch-Based Carbon Fibers>
[0204] Following the above guidelines, determine the cross-sectional shape, flatness, defect number density, tensile strength, tensile modulus, and area ratio of a specific region of pitch-based carbon fiber. The results are shown in Table 1. In Table 1, "area ratio" refers to the ratio of the area of a specific region.
[0205] [Cross-sectional shape, flatness]
[0206] The cross-sectional shape and flatness of pitch-based carbon fibers were obtained by the following method: according to JIS R7606:2000, a laser shape measuring device was used, with the measuring range set to 0° to 180°, and the cross-section of the pitch-based carbon fiber was rotated every 10° to measure the shape of the outer perimeter of the cross-section. The laser shape measuring device used was a Mitutoyo LSM-500S laser scanning micrometer.
[0207] [Defect Count Density]
[0208] Prepare 30 to 50 pitch-based carbon fibers (monofibers) with a length of 25.0 mm. Perform tensile tests according to JIS R7606:2000 as described above, and determine the defect number density (λ) based on the Weibull distribution diagram. av ).
[0209] [tensile strength]
[0210] The average tensile strength obtained from the tensile tests used to create the Weibull distribution map was set as the tensile strength of the pitch-based carbon fiber. Using Comparative Example 1 as a benchmark, the tensile strength improvement rate was calculated, and pitch-based carbon fibers with a tensile strength improvement rate of 130% or more were set as qualified.
[0211] [Tensive Modulus of Elasticity]
[0212] The average value of the tensile modulus of elasticity obtained from the tensile test when making the Weibull distribution map is set as the tensile strength of the pitch-based carbon fiber.
[0213] [Ratio of the area of a specific region]
[0214] SEM (Scanning Electron Microscope) was used to observe randomly selected sections of pitch-based carbon fibers along a direction perpendicular to the section, and SEM images were obtained. The SEM used was a JSM-6500F manufactured by Nippon Egis Corporation.
[0215] As conditions for acquiring SEM images, the magnification was set to 10,000x and the accelerating voltage was set to 5kV.
[0216] The SEM image was analyzed using the image processing software "ImageJ (vl.52)". Specifically, the SEM image was binarized to obtain a binarized image of the cross-section. The binarized image was then edited by depicting the black areas as line segments to obtain an edited image of the cross-section. For the edited image, the straightness of each line segment in the cross-section was evaluated using fractal dimension analysis to determine line segments with a value D = 1.2 or lower. Line segments with a value D = 1.2 or lower were defined as "graphene sheets".
[0217] The line segment with the maximum length of the outline of the given cross section in the edited image (i.e., the maximum length of the straight line connecting any two points of the outline, which is the diameter in the case of a circle and the major axis in the case of an ellipse) is defined as the "boundary surface".
[0218] The image is analyzed using the program described in "Python (v3)" (open source), covering the entire cross-section, to determine the orientation angle of each graphene sheet (line segments with D = 1.2 or less) relative to the boundary surface. The angle at the intersection of the line containing the boundary surface and the line containing the graphene sheet is then set as the orientation angle.
[0219] Using ImageJ (vl.52), the area (specific region) occupied by graphene sheets oriented at an angle of 60° to 120° (line segments with D = 1.2 or less and an orientation angle of 0° to 120°) is set to black for display, and the specific region in the cross-section is identified. Using ImageJ (vl.52), the area of the specific region and the area of the cross-section are calculated. The area of the specific region is divided by the area of the cross-section to obtain the ratio of the area of the specific region.
[0220] For the same cross section as the pitch-based carbon fiber, five identical measurements were performed, and the average of the area ratios of the specific regions obtained from the five measurements was set as the area ratio of the specific regions of the pitch-based carbon fiber.
[0221] Table 1
[0222]
[0223] As shown in Table 1, the pitch-based carbon fibers of Examples 1 to 3 have low defect number densities and excellent tensile strength. In particular, the pitch-based carbon fiber of Example 3 has a particularly low defect number density and a tensile strength exceeding 4000 MPa.
[0224] On the other hand, in Comparative Example 1, because a spinning nozzle with an aspect ratio of 1 was used, the pitch-based carbon fiber became a simple radial structure. Therefore, the effect of thermal shrinkage during the graphitization process was greater, resulting in a high defect density and low tensile strength.
[0225] Comparative Example 2, due to the use of anisotropic pitch with a viscosity as high as 120 Pa·s for melt spinning, has a high defect number density and low tensile strength. Furthermore, in Comparative Example 2, there is a tendency for the tensile modulus of elasticity to also decrease.
[0226] Comparative Example 3, due to the use of anisotropic pitch with a viscosity as high as 150 Pa·s for melt spinning, has a high defect number density and low tensile strength. Furthermore, in Comparative Example 3, there is a tendency for the tensile modulus of elasticity to also decrease.
[0227] It should be noted that the entire disclosure of Japanese application 2021-093111 is incorporated herein by reference.
[0228] All documents, patent applications and technical standards described in this specification are incorporated herein by reference to each other to the same extent as the specific and separately described documents and technical standards.
[0229] Symbol Explanation
[0230] 10 Graphene Sheets
[0231] 12 Straight lines containing graphene sheets
[0232] Boundary surfaces 30 and 32
[0233] 34 Centers
[0234] 36. Straight lines including boundary surfaces
[0235] 100, 102, 104 pitch-based carbon fibers
[0236] 50 Spinning nozzle ejection orifice
[0237] 70 Import Section
[0238] 90° cone
[0239] α Orientation angle
[0240] L Forming section length
[0241] θ cone angle
[0242] a. Short side of the nozzle
[0243] b. Long side of the nozzle
[0244] 200 spinning nozzles
Claims
1. A pitch-based carbon fiber having a defect number density of 40 defects / m or less, and a cross-sectional shape perpendicular to its length direction that is elliptical with an flatness ratio of 0.25 or less, and having a boundary surface along the major axis of the elliptical cross-section. The pitch-based carbon fiber is manufactured by a method comprising a melt spinning step of ejecting molten anisotropic pitch from a spinning nozzle and spinning it. The spinning nozzle has an inlet portion for introducing the molten anisotropic pitch, an outlet portion, and a cone portion connecting the inlet portion and the outlet portion. The cone angle of the cone portion is 90° to 150°. The ratio of the length of the long side of the circumscribed rectangle of the shape of the nozzle's outlet to the length of the short side of the circumscribed rectangle is 1.5 to 10.
0. The viscosity of the molten anisotropic pitch is 20 Pa·s to 80 Pa·s.
2. The pitch-based carbon fiber according to claim 1, wherein, The pitch-based carbon fiber includes graphene sheets, and the area occupied by the graphene sheets oriented at an orientation angle of 60° to 120° relative to the boundary surface accounts for more than 60% of the area of the cross section.
3. The pitch-based carbon fiber according to claim 2, wherein, The shape of the cross section is an ellipse with a flatness ratio of less than 0.
2.
4. The pitch-based carbon fiber according to claim 1, wherein, The defect number density is less than 30 per m.
5. The pitch-based carbon fiber according to claim 1, wherein, The tensile modulus of elasticity is above 400 GPa.
6. The pitch-based carbon fiber according to claim 5, wherein, The tensile modulus of elasticity is above 440 GPa.
7. The pitch-based carbon fiber according to claim 1, wherein, The shape of the ejection hole is rectangular or elliptical.
8. The pitch-based carbon fiber according to claim 1, wherein, The viscosity of the anisotropic asphalt is 30 Pa·s to 60 Pa·s.
9. The pitch-based carbon fiber according to claim 1, wherein, The spinning speed in the melt spinning process is 200 m / min to 500 m / min.
10. The pitch-based carbon fiber according to claim 1, wherein the manufacturing method comprises a graphitization step of subjecting the carbonized pitch-based carbon fiber precursor to heat treatment to graphitize it after the melt spinning step. The temperature of the heat treatment in the graphitization process is 2000℃~2900℃.
11. A fiber-reinforced plastic comprising pitch-based carbon fibers according to any one of claims 1 to 6.
Citation Information
Patent Citations
Production of pitch based carbon fiber
JP1985155714A
Graphite fiber
JP1986006316A
High-strength, high-modulus pitch-based carbon fiber
JP1993029689B2
Advanced traffic system capable of indicating congestion state
JP2021093111A
Pitch-based carbon fiber and production thereof
JP1989282316A